2023
DOI: 10.3390/su15064769
|View full text |Cite
|
Sign up to set email alerts
|

Application of Phosphogypsum and Organic Amendment for Bioremediation of Degraded Soil in Tunisia Oasis: Targeting Circular Economy

Abstract: This study was conducted at the Institute of Arid Regions of Gabes in Tunisia. Three plots were left as controls and received no input, three plots were amended with cattle manure with a dose equivalent to 37.5 t/ha, and nine plots were amended with phosphogypsum in three doses (12.5 t/ha, 25 t/ha, and 50 t/ha), with three repetitions for each dose. A pot test to determine the germination index and radioactivity analysis was carried out in the laboratory. The results showed that organic manure amendments and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Long-term studies [70,71] have shown that the application of phosphogypsum on irrigated saline chernozem soils has a positive effect on the anion-cation composition of water leaching and the degree of salinity of these soils [72,73]. In experimental plots, with the application of phosphogypsum during irrigation and without it, a sulphate type of salinity was observed in terms of the anion composition.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term studies [70,71] have shown that the application of phosphogypsum on irrigated saline chernozem soils has a positive effect on the anion-cation composition of water leaching and the degree of salinity of these soils [72,73]. In experimental plots, with the application of phosphogypsum during irrigation and without it, a sulphate type of salinity was observed in terms of the anion composition.…”
Section: Discussionmentioning
confidence: 99%
“…It is rich in vital nutrients like phosphorus, calcium, magnesium, and more, which can reduce the need for additional fertilizers . Other benefits include eliminating the surface crust of the soil, reducing the viscosity of the soil, increasing the permeability of the soil , and increasing yield while preventing certain crop diseases. Phosphogypsum has been used to improve acidic soil by Villalón Fornés et al and have been tested corn pot planting experiments by Carvalho et al . Its positive effects on soil structure have been well-documented, such as promoting flocculation between soil particles and enhancing soil aggregation .…”
Section: Introductionmentioning
confidence: 99%
“…The variability complicates the development of a universal purification method. However, bioremediation emerges as a beacon of hope in this scenario. , It effectively uses organisms to absorb, transform, or immobilize contaminants, offering adaptability and environmental compatibility . Its efficacy is underscored by successes such as the extraction of heavy metals from phosphogypsum in Florida, a region notorious for its high radioactive content in phosphogypsum…”
Section: Introductionmentioning
confidence: 99%